MENGGALI NILAI LAIN PRAKTIK AKUNTANSI MANAJEMEN PERSPEKTIF SOSIOLOGIS - INTERPRETIF (Studi Pada PT. Ttrm – Mdn) - Bambang Haryadi (Universitas Trunojoyo Madura, 2012)
Interpretive-perspective has changed the traditional view point of accounting information as a mean of achieving goals. Interpretive-perspective could not simply suggests that mainstream accounting is the only mean of achieving goals when accounting discipline has ontologically proposed pre-given assumptions on organizational and individual objectives. This paper aims to investigate and to construct management accounting value called “sang lain” which was practiced in a company, by utilizing a research method called interpretive. The study result suggests that there were many other local management values in the company which have been practiced since long time ago and have been the strength and motivation of company business. The “sang lain” value of pricing, investment planning, budgeting, and revenue has been understood and been used as the basis of company practice